MENTAL FEATURES OF PROVERBS - Muhsinovna, Jurayeva Bibish; Abdumalikovna, Tosheva Dildora; Ubayduiiaevna, Nurova Yulduz (International Journal of Psychosocial Rehabilitation, 2020)
Zoonyms are parts of the proverbs and play an important role in creating a figurative image based on people’s worldview and cultural life. Zoonym component proverbs are found in almost all world languages. This is because humans and animals have lived side by side for thousands of years. Therefore, animals play a special role in the daily activities and cultural life of people. The linguistic units that emerge as a result of the unity of national-cultural and ethnic differences, mental features are recognized as important concepts to be studied in the field of linguocultural science. The issue of studying the essence of their meaning and the extent of their application in everyday life is analyzed in the context of linguocultural science. Finding solutions to problems related to language and culture and increasing the amount of research will be an important factor in determining the development of linguocultural science. This article discusses the importance of Uzbek and English zoonym component articles in reflecting the national, cultural and mental characteristics of both nations and ethnicities. The articles identify individual and universal nouns created by the example of zoonym, and identify common aspects of English and Uzbek people.